Pengaruh Tingkat Kemiskinan dan Jumlah Penduduk Terhadap Indeks Pembangunan Manusia (IPM) Kabupaten Batang Hari 2011 -2019 - Jasasila Jasasila (Universitas Batanghari Jambi, 2020)
Human Development Index is used to measure how much impact arises from efforts to increase the ability of basic human capital. Human Development is a component of development through empowerment of the population that focuses on increasing the human base, judging from the population of Batang Hari Regency which is fluctuating and has the potential for human resources ready to be empowered. The implementation of regional autonomy gives flexibility to the Regional Government of Batang Hari Regency to carry out regional development more independently. Besides that what needs to be considered is the growth of the poor population, in Batanghari District the development of the poor population has also fluctuated, where in 2019 there was a decrease of 26.53% from the previous year. To measure poverty, BPS uses the concept of ability to meet basic needs approach. This is done in Batang Hari Regency, using data from 2011 - 2019. The type of data used in this study is Time Series data, which is the type of data consisting of variables collected according to the order of time within a certain timeframe, while the analytical methods used in This research is a quantitative method. Quantitative analysis is used to determine the Effect of Poverty Rate and Population Number on the human development index (HDI) in Batang Hari District 2011-2019. To analyze the influence of data analysis, this is done by using multiple linear regression models using Eviews program version 9.0. poverty level and Population simultaneously or together have a very significant effect on the Human Development Index in Batang Hari District 2011-2019. In this study the R2 value is 0.975311 which means a set of dependent variables (Poverty Rate and Population Number) in the model can explain the Independent variable by 97.53%. While the rest is explained by other variables outside the model that are not examined. Human Development Index (HDI) of Batang Hari 2011-2019 is 32.58 assuming other variables (Poverty Rate and Population Growth Rate are fixed or 0) From the equation it is known that poverty variable shows a coefficient of 0.03 meaning that if there is an increase in poverty level of 1 unit it will increase the HDI by 0.03% with the assumption that the Population Variable is 0. Whereas for the Total Population from the data processing, the result is 0.00013, meaning that every 1 person increase will increase the Human Development Index (HDI) by 0.00013%.